16 The significance of intimate relationships at end of life: experiences of young adults with life-limiting or life-threatening conditions. Issue 3 (1st September 2017) - Earle, Sarah; Blackburn, Maddie; Cooke, Alison
Abstract : Introduction: Until relatively recently, children and young people with life-limiting and/or life-threatening conditions (LLTCs) were not expected to live into adulthood. Today there are approximately 55 000 people with a LLTC living in the UK (Norman & Fraser 2014). Given its demographic infancy, very little empirical work has been carried out with this population and even less is known about the needs and expectations of young people with LLTCs on sex and relationships. Aim: The project aimed to explore the significance of intimate relationships for young adults with LLTCs focusing, in particular, on the impact of this on their sense of wellbeing. Method: The study was carried out within a qualitative framework. Twelve participants were recruited to the project via a network of hospices and organisations that support young adults with LLTCs in England. Three focus groups were held in April 2017. The focus groups were hosted by two hospices and one organisation that provide support to young people with LLTCs. Results: A thematic analysis of the focus group data highlighted three themes relating to the significance of intimate relationships for young adults with LLTCs. These are: (1) intimate relationships as rite of passage; (2) the significance of intimate relationships on happiness and wellbeing, and (3) social isolation and participatory barriers. Conclusion: Young adults with LLTCs experience a combination of social exclusion and social isolation which impacts on their participatory opportunities. This lack of participatory opportunity subsequently impedes their ability to form meaningful, intimate relationships that could contribute to happiness and enhance wellbeing. Reference: . Norman P, Fraser L. Prevalence of life-limiting conditions in children and young people in England: Time trends by area type. Health and Place2014;26:171–179. DOI: 10.1016/j.healthplace.2014.01.002.